Chemical Vapor Deposition-Fabricated Manganese-Doped and Potassium-Doped Hexagonal Tungsten Trioxide Nanowires with Enhanced Gas Sensing and Photocatalytic Properties - Pin-Ru Chen; Hsuan-Wei Fu; Shu-Meng Yang; Kuo-Chang Lu (Nanomaterials, 2022)
Owing to its unique and variable lattice structure and stoichiometric ratio, tungsten oxide is suitable for material modification; for example, doping is expected to improve its catalytic properties. However, most of the doping experiments are conducted by hydrothermal or multi-step synthesis, which is not only time-consuming but also prone to solvent contamination, having little room for mass production. Here, without a catalyst, we report the formation of high-crystallinity manganese-doped and potassium-doped tungsten oxide nanowires through chemical vapor deposition (CVD) with interesting characterization, photocatalytic, and gas sensing properties. The structure and composition of the nanowires were characterized by transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS), respectively, while the morphology and chemical valence were characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), respectively. Electrical measurements showed that the single nanowires doped with manganese and potassium had resistivities of 1.81 × 0−5 Ω·m and 1.93 × 10−5 Ω·m, respectively. The doping contributed to the phase transition from monoclinic to metastable hexagonal for the tungsten oxide nanowires, the structure of which is known for its hexagonal electron channels. The hexagonal structure provided efficient charge transfer and enhanced the catalytic efficiency of the tungsten oxide nanowires, resulting in a catalytic efficiency of 98.5% for the manganese-doped tungsten oxide nanowires and 97.73% for the potassium-doped tungsten oxide nanowires after four hours of degradation of methylene blue. Additionally, the gas sensing response for 20 ppm of ethanol showed a positive dependence of doping with the manganese-doped and potassium-doped responses being 14.4% and 29.7%, respectively, higher than the pure response at 250 °C. The manganese-doped and potassium-doped tungsten oxide nanowires are attractive candidates in gas sensing, photocatalytic, and energy storage applications, including water splitting, photochromism, and rechargeable batteries.